Hierarchical organization of speech perception in human auditory cortex - Humphries, Colin; Sabri, Merav; Lewis, Kimberly; Liebenthal, Einat (Frontiers in Neuroscience, 2014)
Human speech consists of a variety of articulated sounds that vary dynamically in spectral composition. We investigated the neural activity associated with the perception of two types of speech segments: (a) the period of rapid spectral transition occurring at the beginning of a stop-consonant vowel (CV) syllable and (b) the subsequent spectral steady-state period occurring during the vowel segment of the syllable. Functional magnetic resonance imaging (fMRI) was recorded while subjects listened to series of synthesized CV syllables and non-phonemic control sounds. Adaptation to specific sound features was measured by varying either the transition or steady-state periods of the synthesized sounds. Two spatially distinct brain areas in the superior temporal cortex were found that were sensitive to either the type of adaptation or the type of stimulus. In a relatively large section of the bilateral dorsal superior temporal gyrus (STG), activity varied as a function of adaptation type regardless of whether the stimuli were phonemic or non-phonemic. Immediately adjacent to this region in a more limited area of the ventral STG, increased activity was observed for phonemic trials compared to non-phonemic trials, however, no adaptation effects were found. In addition, a third area in the bilateral medial superior temporal plane showed increased activity to non-phonemic compared to phonemic sounds. The results suggest a multi-stage hierarchical stream for speech sound processing extending ventrolaterally from the superior temporal plane to the superior temporal sulcus. At successive stages in this hierarchy, neurons code for increasingly more complex spectrotemporal features. At the same time, these representations become more abstracted from the original acoustic form of the sound.